Real Hamiltonian Forms of Affine Toda Models Related to Exceptional Lie Algebras - Gerdjikov, V.S.; Grahovski, G.G. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
The construction of a family of real Hamiltonian forms (RHF) for the special class of affine 1+1-dimensional Toda field theories (ATFT) is reported. Thus the method, proposed in [1] for systems with finite number of degrees of freedom is generalized to infinite-dimensional Hamiltonian systems. The construction method is illustrated on the explicit nontrivial example of RHF of ATFT related to the exceptional algebras E₆ and E₇. The involutions of the local integrals of motion are proved by means of the classical R-matrix approach.